Implementasi Manajemen Bandwidth VoIP Pada IP-PBX Menggunakan Routerboard di Jaringan Intranet - Nadhirotun Maulidiyah; Martono Dwi Atmadja; Mohammad Abdullah Anshori (Politeknik Negeri Malang, 2020)
The growing number of internet applications and their users can affect the quality of the internet, each application has different traffic needs. In addition, bandwidth management can also lend bandwidth that has been allocated in accordance with its priorities in order to optimize existing bandwidth usage. Regulating and limiting internet bandwidth usage is indeed an important thing when our internet connection is limited. We need to limit the bandwidth quota of each user connected to the Mikrotik Router. In Mikrotik Router itself, there are features that can limit bandwidth, namely simple queue and queue tree. In the use of VoIP services, bandwidth management is required to manage traffic on the network, the appropriate bandwidth settings can optimize the speed of data transmission. Looking at the internet needs, this research designs an implementation of bandwidth management using routerboard, which will be applied to IP-PBX and use raspberry pi as a server. The results of the research on bandwidth management implementation in simple queue and queue tree is each able to serve 6 users with PCMU codecs, from the test obtained packet loss value of 0.00% from 3 clients, and jitter has an average value of 167.37% from 3 clients.